The Fiber To The Home Internet services quality of Lao Telecommunication Public Company in Luang Prabang Province - Sipasueth, Khamsouk; Yangsanesay, Chahue; Indavong, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of this research were to examine Customers’ decisions to use Fiber to the Home (FTTH) internet services; to study customers’ opinions regarding the quality of FTTH internet services; and to analyze the service quality factors influencing customers’ decisions to use FTTH internet services provided by Lao Telecommunication Public Company in Luang Prabang Province. The study employed a questionnaire as the data collection instrument and collected data from 383 customers who use FTTH internet services of Lao Telecommunication Public Company in Luang Prabang Province. The reliability of the questionnaire, measured by Cronbach’s alpha, was 0.953. The statistical methods used for data analysis included frequency, percentage, mean, standard deviation, and binary regression analysis. The results revealed that customers demonstrated a strong intention to continue using FTTH internet services and to recommend the services of Lao Telecommunication Public Company to others. Overall, customers reported a high level of satisfaction with the service. Regarding customers’ opinions on the quality of FTTH internet services provided by Lao Telecommunication Public Company, Luang Prabang Branch, the overall service quality was rated as good. Among the service quality dimensions, tangibles received the highest rating, followed by reliability, empathy, and responsiveness, while assurance was rated the lowest. The analysis of service quality factors influencing customers’ decisions to use FTTH internet services indicated that three service quality dimensions tangibles, responsiveness, and empathy had a positive and statistically significant effect on customers’ decisions at the 0.05 significance level.